ANALISIS EFEKTIVITAS SISTEM PENGENDALIAN INTERNAL PENGGUNAAN DANA DESA - Sahri, Yulian (Balance : Jurnal Akuntansi dan Bisnis, 2020)
The enactment of Law No. 6, 2014 on Villages has given the opportunity for villages to manage their own finances. In 2017 the budget allocated by the central government amounted 720 million rupiahs per village. The central government needs to apply control and monitoring on the fund to ensure that there is no leakage and fraud in its spending. The survey results conducted by ICQ in 2016 show that there are 62 cases of corruption of the village fund already under investigation, with a total loss to the state reaching 18 billion rupiahs. One of the causes of the high number of fraud cases is the weak enforcement of internal control. The aim of this research is to analyze the effectiveness of Internal Control System (SPI) on the use of village fund at Kepayang village, Lempuing district, Ogan Komering Ilir Regency. This research uses a qualitative approach, the data collection for this research is conducted by means of interview, observation, and documentation. There are 4 participants in this research, namely Village Head, Village Secretary, Village Treasurer, and Kampong Society Representative Body. The internal control system in Kepayang village is running sufficiently well with a percentage of 65. This is because many of the components of control in the village government are not implemented.